Pengaruh Disiplin Belajar dan Minat Belajar terhadap Hasil Belajar PAI Siswa di SMA Negeri 1 Kendari - Siti Nur Rahmawati; Muhammad Syarwa Sangila (Tarbiyatul Akhyar: Jurnal Pendidikan, 2026)
The aims of this research are (1) to determine the influence of learning discipline on students' PAI learning outcomes, (2) to determine the influence of learning interest on students' PAI learning outcomes, (3) to determine the joint influence of learning discipline and learning interest on student PAI learning outcomes. The data collection techniques used are documentation and questionnaires, while the data analysis techniques use descriptive analysis techniques and inferential analysis. This research uses a type of causality survey research with a quantitative approach. The total population is 160 students and the sample is 62 students. The results of research at SMAN 1 Kendari, based on data analysis concluded with (1), there is a significant influence between learning discipline on student PAI learning outcomes, this is proven by the results of the significance test of 0.005<0.05 and the simple coefficient value (R) 0.356> rtable 0.2500, with an influence contribution of 12.7% (2), there is a significant influence between interest in learning on student PAI learning outcomes, this is proven by a significance value of 0.000<0.05 and a simple coefficient (R) value of 0.498>rtable 0.2108, with an influence contribution of 24.8% (3), there is a joint significant influence between learning discipline and learning interest on students' PAI learning outcomes. This is proven by a significance value of 0.000<0.05 and fcount 9.964> ftable 3.154 and simple coefficient value (r) 0.502> rtable 0.2500, with an influence contribution of 25.2%